ISOLASI DAN KARAKTERISASI FISIOLOGIS PGPR DARI RIZOFER TANAMAN KACANG TANAH (Arachis hypogaea) VARIETAS LOKAL MAYBRAT - Kristi Lenci Patty; Laury Chara Marcia Huwae; Yulia Yunita Mayor (LPPM Politeknik Saint Paul Sorong, 2023)
Sustainable agriculture systems utilizing PGPR (Plant Growth-Promoting Rhizobacteria) have the potential to increase due to their environmentally friendly and practical nature, to replace the increasing use of chemical-based fertilizers and pesticides. Peanut (Arachis hypogea L) local variety Maybrat is a plant that has the potential to be isolated by bacteria in its rhizosphere area to be used as a biostimulant candidate. This study aimed to determine the type of rhizobacteria in the rhizosphere area associated with local varieties of peanuts in the Maybrat Regency and obtain superior rhizobacteria for biostimulants (PGPR). A total of 8 isolates were successfully isolated from peanut rhizosphere and based on physiological characteristics showed that KM2 isolates produced the highest IAA of 2,625 mg l-1, and KM8 isolates produced the highest GA3 concentration of 4.19 mg l-1. KM7 isolates produce salicylates with the highest concentration of 0.788 mg l-1, while KM3 isolates produce the highest type of catechols of 1.89 mg l-1. The KM8 isolate is capable of dissolving the highest phosphate of 12.46 mg l-1. Cyanide production tests showed that all eight bacterial isolates did not have the ability to produce cyanide. Based on physiological characteristics, it shows that these 8 isolates have the potential to be biostimulants and biofertilizers for plants.